Job Satisfaction At The Mochachino Cigarette Factory: The Influence Of Job Conflict, Job Stress And Work Environment - Boby Ariyanto; Dewi Andriani; Sumartik Sumartik (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Human Resources (HR) are the main assets of an organization, so that the actors (people) must be empowered in a balanced and humane manner, so that the company must create job satisfaction. Human resource management has several goals, one of which is organizational goals/company goals and also to achieve employees' personal goals. The purpose of this research is to determine the influence of work conflict, work stress and work environment on job satisfaction of permanent employees of the Mochacino Cigarette Factory. The approach used in this research is quantitative by distributing questionnaires to 85 sources quoted through the non-probability sampling method used, namely total sampling or saturated sampling. How to analyze the information using multiple linear regression of the IBM SPSS version 24 software program with findings that answer the hypothesis that there is a partial and simultaneous influence of work conflict, work stress and work environment on Job Satisfaction.